Language problems encountered by undergraduate EFL students in writing scientific papers for publication - Hartono Hartono; Ollyvia Putri Angella; Choiril Anwar (Universitas Islam Sultan Agung, 2026)
College students are currently also required to publish articles in scientific journals. This requirement is beneficial for their research and writing development; however, writing scientific articles is not easy, especially for undergraduate students. This paper investigates the language problems encountered by undergraduate EFL students when writing scientific papers for publication. It is a mixed-methods study involving both quantitative and qualitative data collection and analysis. The respondents were 25 undergraduate students writing English papers for publication and 3 lecturers supervising them. Selected. They were from an English Education program at a university in Semarang, Central Java, Indonesia, and were selected purposively. The data were collected through a 10-item closed-ended questionnaire and interviews with both students and lecturers. The quantitative data were analysed descriptively, while the qualitative data were analysed thematically. The results indicate that the primary language problems faced by undergraduate students in writing papers for publication are vocabulary selection, phrase structure, and article usage. They also have significant challenges with the correct use of tenses, sentence structure, word class, and subject-verb agreement. Though facing problems, the students reported that they were able to solve them by using AI tools. This implies that incorporating technology into the teaching of writing can be beneficial.